Inpatient Care Unit in Children and Adolescents With Autism Spectrum Disorder: Benefits, Difficulties, and Conditions of Hospitalization. Issue 3 (12th March 2022) - Ozbaran, Burcu; Kose, Sezen; Barankoglu, Ilayda; Dogan, Nurhak
Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that affects social interactions and behavior. The number of children and adolescents with ASD treated in mental health services has been growing in recent years. Knowing clinical and familial characteristics of hospitalized patients with ASD and multidisciplinary approach are crucial for children and adolescents mental health professionals. In this study, 253 Turkish children and adolescents, with and without ASD, treated in psychiatry inpatient care unit were examined. Applied approaches such as medical consultation areas, psychiatric management of mothers, and pharmacological treatment during hospitalization, were studied. In addition to familial and clinical characteristics of patients with ASD, the benefits and the hospitalization conditions were evaluated. Patients with ASD showed a higher tendency on having relatives with a psychiatric disorder than the patients without ASD. A significant difference was found in terms of age, sex, and intellectual functioning, whereas length of stay did not differ drastically. Also, suicide attempts were significantly higher in patients without ASD than in patients with ASD. This study eases the management of hospitalized ASD patients with giving important information of clinical and familial characteristics.